Analysis of the Inaportnet System That Affects the Ship Service of PT Kartika Samudra Adijaya at the Port of Samarinda - Muhammad Idris; Dodik Widarbowo; I Komang Hedi Pramana Adiputra; Elisabeth Amanda Yvonne Kartikawardani (Asian Journal of Social and Humanities, 2024)
This study aims to determine the implementation of the inaportnet system that affects ship services at PT Kartika Samudra Adijaya at Samarinda Port. The method used in this study is qualitative with a descriptive approach. Data analysis is a qualitative approach to primary data through observation, documentation and secondary data in statutory studies, books or literature related to vehicle loading systems on board. Based on research on the preparation of ship arrival, during the ship's arrival in the port area, preparation for ship departure, and when the ship departs, It can be concluded that the new inaportnet system was only implemented in October 2022. In adjusting to the new system, several obstacles are still found, such as the lack of guidance of KSOP officers in using the new system and the lack of socialisation from the city authorities to service users (agents). The efforts include holding regular training sessions on the flow of the internet system for officers and service users.